Linguistic Formation in the Poem “Their Blood” by Ibrahim Nasrallah:‎ Space and Significance - Bani Domi, Khalid Qasim (Dirasat: Human and Social Sciences, 2025)
Objectives: This study engages with a poem by the Jordanian poet and novelist Ibrahim Nasrallah, characterized by its high linguistic and artistic qualities, as well as its unique stylistic and aesthetic features. The poem under analysis is "Their Blood," which, to the best of my knowledge, has not previously been the subject of analytical studies or critical readings. The primary aim of this research is to reveal the meanings and implications generated by its linguistic composition through an exploration of the psychological emotions presented, which serve as an interpretive key and provide a significant contextual backdrop for illuminating the text. Methods: The study adopts a descriptive methodology to examine the techniques of linguistic composition in the poem across four linguistic levels: phonetic, morphological, lexical, and syntactic. An analytical framework is employed to assess these levels, thereby uncovering their semantic dimensions and highlighting their stylistic and aesthetic characteristics. Results: The study identifies several key findings, the most notable of which is that the term "Their Blood" functions as the central motif of the poem and simultaneously serves as its title. The repetition of this term significantly contributes to the poem’s cohesion and facilitates the achievement of its organic unity and distinctive artistic structure. Conclusion: This study elucidates the manifestations of linguistic composition in the poem "Their Blood," revealing its semantic dimensions, stylistic traits, and aesthetic qualities. It also opens avenues for further research by inviting scholars to investigate additional linguistic and stylistic issues inherent in the poem and to employ alternative critical approaches to linguistic analysis, such as psychological frameworks and keyword methodologies.